The Influence of Macroeconomic Effects on Company Financial Performance with CPO Prices as an Intervening Variable in Palm Oil Companies Listed on the Indonesia Stock Exchange (IDX) in 2011-2021 - Ani Apriani; Nardi Sunardi; Sahroni (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to determine the effect of Inflation, interest rates and exchange rates on company financial performance with CPO prices as an intervening variable for oil palm companies listed on the IDX for the 2011-2021 period. The data used in this research is secondary data. This type of research uses an associative method with a quantitative approach. The number of samples in this study is  110 data based on the criteria obtained for 11 periods with the Eviews 12 testing tool. The analysis technique used is panel data regression and the Sobel test. The results of this study include: (1) Inflation has a positive but not significant effect on CPO prices, (2) Interest rates have a negative and significant effect on CPO prices, (3) The rupiah exchange rate has a negative but not significant effect on CPO prices, (4) Inflation, interest rates and the rupiah exchange rate simultaneously have a significant effect on CPO prices, (5) Inflation has a negative but not significant effect on the performance of palm oil companies, (6) Interest rates have a positive but not significant effect on the performance of palm oil companies, (7) The exchange rate has a negative and significant effect on the performance of palm oil companies, (8) CPO prices have a positive and significant effect on the performance of palm oil companies, (9) Inflation, interest rates,the rupiah exchange rate and CPO prices simultaneously affect the performance of palm oil companies, (10) CPO prices cannot mediate the effect of Inflation on the performance of palm oil companies, (11) CPO prices can edition of the effect of interest rates on the performance of palm oil companies, and (12) CPO prices cannot mediate the effect of the exchange rate on the performance of palm oil companies.